Nonclassical behavior of the mouse CD1 class I-like molecule - Teitell, M; Holcombe, H R; Brossay, L; Hagenbaugh, A; Jackson, M J; Pond, L; Balk, S P; Terhorst, C; Peterson, P A; Kronenberg, M (The Journal of immunology (1950), 1997)
The mouse CD1 (mCD1) molecule is a class I-like molecule that is encoded outside of the MHC. We show here that mCD1 shares several properties with Ag-presenting class I molecules, including a requirement for beta2-microglobulin for stable cell-surface expression in T lymphocyte transfectants and thymocytes. mCD1 is also capable of binding to mouse CD8alphabeta heterodimers participating in the activation of CD8+ T cells in a manner similar to classical class I molecules. However, mCD1 surface expression is not decreased at high temperatures in cells that lack the transporter associated with Ag processing (TAP), including both RMA-S and Drosophila melanogaster cells. The data indicate that mCD1 does not require TAP to be expressed in a stable fashion at the cell surface. We speculate that the ability of mCD1 to reach the cell surface in transporter-deficient cells may reflect its ability to present a distinct set of ligands. The properties of mCD1 described here can account, in part, for the selection of the diverse populations of T cells that are known to be mCD1 reactive.